2013
DOI: 10.1016/j.expneurol.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing factor in the mouse central nucleus of the amygdala: Ultrastructural distribution in NMDA-NR1 receptor subunit expressing neurons as well as projection neurons to the bed nucleus of the stria terminalis

Abstract: Corticotropin-releasing factor (CRF) and glutamate are critical signaling molecules in the central nucleus of the amygdala (CeA). Central amygdala CRF, acting via the CRF type 1 receptor (CRF-R1), plays an integral role in stress responses and emotional learning, processes that are generally known to involve functional NMDA-type glutamate receptors. There is also evidence that CRF expressing CeA projection neurons to the bed nucleus of the stria terminalis (BNST) play an important role in stress related behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 77 publications
2
23
0
Order By: Relevance
“…Most of the effects of the VDRA were restricted to process formation around the cell body; this is similar to the microtubule cytoskeletal system found in the dendritic nucleation assembly. This finding confirms the presence of VDR and its likely restriction to d cell body plus its role in facilitating short dendrite like process formation while NMDA R is located on the processes and facilitates long process formation; similar to the findings of Beckerman et al [37].…”
Section: Resultssupporting
confidence: 90%
“…Most of the effects of the VDRA were restricted to process formation around the cell body; this is similar to the microtubule cytoskeletal system found in the dendritic nucleation assembly. This finding confirms the presence of VDR and its likely restriction to d cell body plus its role in facilitating short dendrite like process formation while NMDA R is located on the processes and facilitates long process formation; similar to the findings of Beckerman et al [37].…”
Section: Resultssupporting
confidence: 90%
“…This study directly measured these 16 parameters and compared them to CRF-R1 lacking neurons (eGFP -). Our results 17 suggest that many CRF + neurons share some of these properties with CRF-R1 neurons 18 suggesting a partial overlap in these populations of genetically identified neurons 19(Beckerman et al, 2013). 20 CRF release in the extended amygdala has typically been associated with high-21 frequency, long duration firing of neurons; along with modulatory actions through G-22 protein coupled receptors (Rainnie et al, 1992; Yu and Shinnick-Gallagher, 1998)that the CRF-R1 antagonist, antalarmin, failed to affect light evoked IPSCs 1 in CRF -neurons in BnST and CeA.…”
mentioning
confidence: 79%
“…Further, we and others have reported that CRF antagonism in the bed nucleus of the stria terminalis (BNST) can block the behavioral expression of social defeat (Cooper and Huhman, 2005;Jasnow et al, 2004b). This brain region receives heavy innervation from the CeA by neurons co-expressing CRF and Grin1 (glutamate receptor, ionotropic N-methyl-D-aspartate 1; NR1) receptor subunits (Beckerman et al, 2013). Blockade of this CRF-ergic projection also attenuates the behavioral effects of social defeat (Jasnow et al, 2004b).…”
Section: Introductionmentioning
confidence: 94%